PEMBUATAN DAN UJI ANTIBAKTERI GEL ARANG TEMPURUNG KELAPA TERHADAP BAKTERI Staphylococcus aureus - Kurniawan - Kurniawan; Aisyah Sabila Rosyada; Arif - Mulyanto; Kurnia Ritma Dhanti (Fakultas Biologi | Universitas Jenderal Soedirman, 2023)
Staphylococcus aureus is a Gram-positive coccus that is an opportunistic pathogen, namely as a normal flora and also as a pathogen that causes nosocomial infections. This bacterium is able to adapt and easily undergo mutations, giving rise to new strains that are resistant to antibiotics and pose a threat to human health. Efforts to find active ingredients that are effective against S. aureus continue to be carried out by utilizing coconut product waste, namely coconut shell charcoal, which contains active ingredients in the form of antimicrobial compounds. The material is extracted and made into a gel preparation to make it easier to use. The purpose of this study was to obtain the optimal coconut shell charcoal extract gel formula and determine its ability to inhibit the growth of S. aureus bacteria in vitro. This type of research is true experimental, consisting of five groups, namely positive control, negative control, and concentrations of 3%, 6%, and 9%. The extract was prepared in the form of a gel and tested for antibacterial activity using the diffusion method. The optimal preparation of coconut shell charcoal extract gel was achieved at a concentration of 9%, and the greatest antibacterial inhibition against S. aureus bacteria was also obtained at a gel with a concentration of 9%. The coconut shell charcoal extract gel formula with a concentration of 9% is the optimal gel and has the greatest antibacterial inhibition against S. aureus bacteria.Key Words: antibacterial test, coconut shell charcoal, gel preparation, Staphylococcus aureus